Amino Acid- Essentiality to Human Body (Patan Pragya, 2021)
An amino acid is one of the major building block of protein unit, arranged around the carbon atom in tetrahedral manner. These are classified into essential and non-essential amino acids based on their availability on the body. As many as 300 amino acids, only 20 are standard amino acid for their functional view. Each amino acid i.e. monomers joined with peptide linkage as a result biggest molecule of amino acid forms where larger molecule represented by R-group/s. Rich sources of it are pulses, seeds, non-veg foods as well as animal products. Amino acids play major role in metabolic activities for human beings and supply the energy to the body and get healthy fitness as well as neurotans mitters. Excretion of urea and CO2 also results due to the different reaction occurring in liver and kidney. Metabolic disorder causes phenylketonuria, alkaptonuria, albinism like problems. Detection of amino acids can be done by various measures but mostly utilized method is ninhydr in test, is a chemical process where the development of coloration confirms the presence of amino acid.